INTEGRASI PROJECT BASED LEARNING (PJBL) DAN PENDEKATAN STEM DALAM PEMBELAJARAN BIOLOGI: KAJIAN LITERATUR - Fitriasari, Eka; Juliyanti, Melviana Dwi Juliyanti; Azizah, Jum; Yustika, Diana; Fitriannisa, Syifa; Mujhiyaningsih, Annisa; Usman (EDUBIOLOCK, 2025)
This study aims to analyze the effectiveness of integrating Project-Based Learning (PjBL) and the STEM approach in biology education. A systematic and descriptive literature review was conducted on articles published from 2016 to 2024 obtained from Google Scholar, SINTA, and Scopus. Articles were selected based on the relevance of the title, abstract, and content. The analyzed data included learning design, integration strategies, educational level, and learning outcomes. Thematic narrative analysis was used. The results from ten reviewed articles indicate that PjBL-STEM integration enhances critical thinking, creativity, problem-solving, and biology concept mastery. It also fosters students’ collaboration, responsibility, and communication. However, challenges such as teacher readiness and limited resources were found. Teacher training and adequate support are necessary to optimize its implementation.